The Silence of the Dead: Ethical and Juridical Significances of the Exhumations at Prestwich Place, Cape Town, 2003-2005 - Jonker, Julian (Department of Private Law, 2014)
This thesis arises from the debates preceding and following the exhumations at Prestwich Place, Cape Town, between 2003 and 2005. A seemingly arcane subject, these unmarked burials places have become sites for far-reaching discussions about history, memory, space, and identity in the city, and indeed the nation. The debates about the graves should be seen as invoking ethico-juridical questions about memory, forgetting and memorialisation. These are questions that are potent in the collective consciousness of a nation still preoccupied with transition, reconciliation and transformation. [...]